The Protective Effect of Nabk Honey Against Pathological Effects of Penicillin and Streptomycin: Histological Structure and Functions of Guinea pigs Liver - Mohammed S.A.Al-Awara, Elham A. S. AL- Shaibanib, Elias M.A.Salihc, Mohammed A.Y.Al-Eryania (Journal of Applied Pharmaceutical Science, 2013)
This study was designed to determine the protective effect of nabk honey as antioxidant against pathological effects of penicillin and streptomycin histological structure and functions of guinea pigs liver. A total of sixty adult male guinea pigs weighting 800-900g were divided into six groups of ten guinea pigs each, and the experiment lasted 30 days. Animals in group I served as control, animals in group 2 were administrated orally with nabk honey 600 mg/kg, animals in group 3 were intraperitoneally (i.p.) injected with penicillin 50000 IU/kg b.w, animals in group 4 in addition penicillin were orally administrated with nabk honey 600 mg/kg, animals in group 5 were (i.p.) injected with streptomycin 50 mg/kg, and animals in group 6 in addition streptomycin were orally administrated with nabk honey 600 mg/kg. The result showed a significant increase in AST, ALT & ALP levels, and a significant decrease in the levels of total protein and albumin, and addition to histopathological changes in penicillin and streptomycin treated guinea pigs when compared to the control guinea pig. The results of honey administration decreased these histopathological changes, the structure of liver and hepatocytes appearance was more or less similar to control group as well its function. The present results indicate that honey may play an important role as cytoprotective and pave the way for further studies on the possible use of honey.
Keywords: Hypoprotictive, Honey, Penicillin, Streptomycin, His